Difunctional oxygen electrocatalyst with asymmetric coordination structure as well as preparation method and application of difunctional oxygen electrocatalyst

By constructing the M@M-N3O-C catalyst, the high symmetry of the M-N4-C type catalyst is broken, and the asymmetric electron distribution and optimized adsorption/desorption of oxygen intermediates are achieved, which solves the problem of insufficient kinetics of existing catalysts and significantly improves the performance of metal-air batteries.

CN119542441APending Publication Date: 2025-02-28HUANGHUAI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411593126.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Due to the high symmetric structure of the existing M-N4-C oxygen electrocatalyst, the electron density distribution is not conducive to oxygen reduction and oxygen precipitation reaction, and the activity kinetics are weak, and it is necessary to develop a catalyst with an asymmetric coordination structure to improve the reaction activity.

Method used

By constructing the M@M-N3O-C catalyst, metal nanoparticles are wrapped with graphite carbon and accurately distributed M-N3O sites on their surfaces, synergistically inducing asymmetric electron distribution, and optimizing the adsorption/desorption capacity of oxygen intermediates.

Benefits of technology

The high specific surface area and porous structure of the catalyst are achieved, which significantly improves the activity and cycle stability of oxygen reduction and oxygen precipitation reactions, and shows excellent power density and ultra-long cycle life in metal-air batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a bifunctional oxygen electrocatalyst with an asymmetric coordination structure and a preparation method and application thereof, a porous layered precursor is formed through an amide reaction between melamine and citric acid, and the special structure and different functional groups of the porous layered precursor provide many sites for insertion and adsorption of transition metal ions; and an asymmetric coordination structure with high active sites can be formed, the electronic structure of transition metal ions is effectively optimized, and the electro-catalytic performance is improved. The bifunctional oxygen electrocatalyst prepared by the invention shows excellent ORR / OER activity under alkaline conditions, and the power density of a zinc-air battery driven by the bifunctional oxygen electrocatalyst as a cathode catalyst reaches up to 226.7 mW cm <-2 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material science and electrocatalytic materials, and specifically relates to a bifunctional oxygen electrocatalyst with an asymmetric coordination structure, a preparation method and an application thereof. Background Art

[0002] Metal-air battery is a new sustainable energy conversion technology, but its large-scale commercialization is still limited by the expensive price of cathode catalysts, especially the need to use precious metals such as Pt and Ru as oxygen electrocatalysts. In order to reduce the production cost of metal-air batteries, it is necessary to develop relatively low-cost non-precious metal catalysts.

[0003] Among the numerous non-precious metal oxygen electrocatalysts currently available, transition metal-nitrogen-carbon (M-N-C, M=Fe, Co) type catalysts are considered to be the most promising bifunctional catalysts to replace precious metals. They have the advantages of low cost, abundant reserves and significant catalytic effect, and have attracted widespread attention as cathode catalysts for metal-air batteries. In particular, recent research results have shown that catalysts with M-N4-C structure effectively regulate the electronic structure of the M 3d orbital due to the coordination between N atoms and M atoms, thereby making M-N4-C exhibit catalytic behavior similar to that of precious metal Pt for O2 adsorption and O=O bond cleavage, improving the kinetics of cathode oxygen reduction (ORR) / oxygen evolution (OER) reactions and showing a four-electron transfer reaction rate. However, M-N4-C type catalysts have a highly symmetrical structure, and the distribution of their electron density is not conducive to the adsorption of ORR / OER reaction intermediates, thereby weakening the catalytic kinetic activity. Therefore, there is an urgent need to develop a strategy to break the uniform symmetry of M‒N4‒C materials, construct catalysts with asymmetric coordination structures, precisely control the geometric configuration and electronic structure of the catalysts, optimize the binding energy of key intermediates, and thereby improve the reaction activity of M‒N‒C type catalysts. Summary of the invention

[0004] The purpose of the present invention is to provide a bifunctional oxygen electrocatalyst with an asymmetric coordination structure, a preparation method and an application thereof, so as to overcome the limitations of the existing M‒N4‒C type geometric structure and electronic structure control technology. The present invention accurately constructs a M@M‒N3O‒C catalyst with an asymmetric structure, in which graphite carbon wraps metal nanoparticles, and atomically dispersed M‒N3O sites are added. The M‒O and M‒M sites in the structure synergistically induce asymmetric electron distribution, optimize the adsorption / desorption capacity of oxygen intermediates, improve the utilization rate and intrinsic activity of metals, and exhibit excellent power density and ultra-long cycle life in the application of cathode catalysts for metal-air batteries.

[0005] The present invention is achieved through the following technical solutions: A method for preparing a bifunctional oxygen electrocatalyst with an asymmetric coordination structure comprises the following steps: S1, dispersing melamine in water and completely dissolving it at a preset temperature to obtain solution A, then adding citric acid solution, continuing to stir and react to obtain solution B; then subjecting solution B to a hydrothermal reaction, obtaining a precipitate after the reaction is completed, and washing and drying the precipitate to obtain a precursor; S2, dispersing the precursor into a mixed solution of water and ethanol; performing a reflux reaction at a preset temperature, then adding an aqueous solution of transition metal ions, continuing the reflux reaction, obtaining a precipitate after the reaction is completed, washing the precipitate, and drying it to obtain a supramolecular assembly; S3. calcining the supramolecular assembly in an inert atmosphere, heating it to a holding temperature at a preset heating rate, holding it for a preset time, and then naturally cooling it to room temperature to obtain a bifunctional oxygen electrocatalyst with an asymmetric coordination structure.

[0006] Furthermore, in step S1, melamine is dispersed in water and completely dissolved at 50°C to 80°C, the concentration of the obtained solution A is 0.1 to 0.3 mol / L, the concentration of the citric acid solution is 0.45 to 1.1 mol / L, the molar ratio of melamine to citric acid is 1:(0.36 to 1), and the stirring reaction time is 10 to 60 min.

[0007] Furthermore, in step S1, the temperature of the hydrothermal reaction is 110°C to 148°C, and the time is 8 to 16 hours.

[0008] Furthermore, in step S2, the volume ratio of water to ethanol in the water-ethanol mixed solution is 1:(1-3), the temperature of the reflux reaction is 80°C-90°C, and the time of the reflux reaction is 3-6h.

[0009] Furthermore, in step S2, the transition metal ion is a cobalt ion or an iron ion, the concentration of the transition metal ion aqueous solution is 0.01-0.1 mol / L, and the molar ratio of the transition metal ion to melamine is 1:(10-75).

[0010] Furthermore, in step S3, the inert atmosphere is an Ar / H2 mixed gas, and the volume ratio of Ar and H2 gas is (90%~95%) / (10%~5%).

[0011] Furthermore, in step S3, the preset heating rate is 0.5-2.5°C / min, the insulation temperature is 500-600°C, and the preset insulation time is 3-6h.

[0012] Furthermore, in step S3, the bifunctional oxygen electrocatalyst with an asymmetric coordination structure can catalyze oxidation and oxygen evolution reactions.

[0013] A bifunctional oxygen electrocatalyst with an asymmetric coordination structure is prepared by adopting the preparation method.

[0014] Application of a bifunctional oxygen electrocatalyst with an asymmetric coordination structure for the preparation of the cathode of zinc-air batteries.

[0015] Compared with the prior art, the present invention has the following beneficial technical effects: 1. The present invention utilizes the amide reaction between melamine and citric acid to form a porous thin-layer structure precursor, which provides a large number of sites for the adsorption and insertion of transition metal ions, and is easy to form a catalyst with high density of single atomic metal sites. The precursor prepared by the technology of the present invention can be extended to other common transition metals in the field of electrocatalysis, and has universal applicability.

[0016] 2 The present invention uses a precursor constructed with dual ligands containing different functional groups (‒NH2, ‒COOH) to chelate transition metal ions, which is conducive to the formation of M‒N and M‒O active sites after high-temperature polycondensation. This asymmetric structure of the catalyst optimizes the adsorption / desorption capacity of oxygen intermediates and significantly improves the intrinsic activity of the catalyst.

[0017] 3. The M@M-N3O-C bifunctional electrocatalyst prepared by the present invention has a high specific surface area and a porous structure, and exhibits excellent ORR / OER catalytic activity and cycle stability under alkaline conditions. The catalyst is further applied to the cathode of a zinc-air battery, and the assembled battery has a high power density and excellent cycle stability, providing a theoretical basis and technical support for the practical application of zinc-air batteries.

[0018] 4. The present invention can prepare an asymmetric high-activity bifunctional oxygen electrocatalyst through a simple heat treatment step, which is easy to operate and has a simple and efficient synthesis process; the raw materials for preparing the catalyst are widely available and low in price, which is conducive to industrial-scale production and application and has high economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a scanning electron microscope photograph of the Fe@Fe-N3O-C catalyst obtained in Example 1.

[0020] Figure 2 This is the ORR performance diagram of the Fe@Fe-N3O-C catalyst obtained in Example 1.

[0021] Figure 3 This is a scanning electron microscope photograph of the Co@Co-N3O-C catalyst obtained in Example 2.

[0022] Figure 4 This is the ORR performance diagram of the Co@Co-N3O-C catalyst obtained in Example 2.

[0023] Figure 5 This is a scanning electron microscope photograph of the Co@Co-N3O-C catalyst obtained in Example 3.

[0024] Figure 6 This is the ORR performance diagram of the Co@Co-N3O-C catalyst obtained in Example 3.

[0025] Figure 7 This is a scanning electron microscope photograph of the Co@Co-N3O-C catalyst obtained in Example 4.

[0026] Figure 8 This is the ORR performance diagram of the Co@Co-N3O-C catalyst obtained in Example 4.

[0027] Fig. 9 This is the ORR stability performance diagram of the Co@Co-N3O-C catalyst obtained in Example 4.

[0028] Fig.10 These are the OER performance diagrams of the catalysts obtained in Examples 1, 2, 3, and 4.

[0029] Fig.11 Polarization curve and power density diagram of zinc-air battery assembled with Co@Co-N3O-C catalyst obtained in Example 4.

[0030] Fig.12 This is the charge and discharge cycle stability performance diagram of the zinc-air battery assembled with the Co@Co-N3O-C catalyst obtained in Example 4. DETAILED DESCRIPTION

[0031] The embodiments of the present invention will be described in detail below in conjunction with the examples. The implementation cases are preferred embodiments of the present invention and should not be used to limit the scope of the present invention. In the following examples, the methods and experimental equipment used are all conventional methods and instruments unless otherwise specified.

[0032] The present invention provides a method for preparing a bifunctional oxygen electrocatalyst with an asymmetric coordination structure, comprising the following steps: S1. Disperse melamine in distilled water and completely dissolve it at 50°C~80°C to obtain a uniform solution, namely solution A, with a concentration of 0.1~0.3 mol / L, then add a citric acid solution with a concentration of 0.45~1.1 mol / L to react, continue stirring and reacting for 10~60 min, to obtain solution B, wherein the molar ratio of melamine to citric acid is 1:(0.36~1); then transfer solution B into a reactor and perform a hydrothermal reaction at a preset temperature and time, the temperature of the hydrothermal reaction is 110°C~148°C, the time is 8~16h, and a precipitate is obtained after the reaction is completed, and the precipitate is washed and dried to obtain a precursor; S2, dispersing the precursor into a mixed solution of distilled water and ethanol, wherein the volume ratio of distilled water to ethanol in the mixed solution is 1:(1-3); performing a reflux reaction at 80°C-90°C for 3-6 hours, and then adding an aqueous solution of transition metal ions, wherein the transition metal ions are cobalt ions or iron ions, the concentration of the aqueous solution of transition metal ions is 0.01-0.1 mol / L, and the molar ratio of transition metal ions to melamine is 1:(10-75), and continuing the reflux reaction for 3-6 hours, after which a precipitate is obtained, and the precipitate is washed and dried to obtain a supramolecular assembly; S3. Transfer the supramolecular assembly to a tubular furnace and then calcine it in an inert atmosphere. The inert atmosphere is an Ar / H2 mixed gas with a volume ratio of (90%~95%) / (10%~5%) between Ar and H2. Heat the mixture to 500~600°C at a heating rate of 0.5~2.5°C / min, keep the temperature for 3-6 hours, and then cool the tubular furnace naturally to room temperature to obtain a bifunctional oxygen electrocatalyst with an asymmetric coordination structure.

[0033] 4 mg of the catalyst sample prepared above was accurately weighed and dispersed in a mixed solution containing 490 µL of ethanol, 490 µL of deionized water and 20 µL of 5 wt% Nafion solution. The mixed solution was then ultrasonicated into a uniform ink-like slurry. 20 µL of the ink-like slurry was dripped onto the rotating disk working electrode and dried for oxygen reduction and oxygen evolution electrochemical performance tests. At the same time, 375 µL of the ink-like slurry was dripped onto a 1 cm 2 The carbon paper with a hydrophobic diffusion layer was dried at 60 °C for 6 h and used as the air cathode. It was assembled into a zinc-air battery with a metal zinc sheet. The electrolyte was a mixed solution of 6 M KOH and 0.2 M Zn(NO3)2. The zinc-air battery performance was tested.

[0034] Example 1 A method for preparing a bifunctional oxygen electrocatalyst with an asymmetric coordination structure comprises the following steps: (1) Weigh 1 g of melamine and disperse it in 60 mL of distilled water. Stir and dissolve it at 80°C to obtain solution A. Then add 5 mL of 1 mol / L citric acid solution and continue stirring to react for 30 min to obtain solution B. Then transfer solution B into a reactor for hydrothermal reaction at 148°C for 10 h. After the reaction is completed, a white precipitate is obtained. The precipitate is washed three times with distilled water and dried in a vacuum oven at 80°C for 12 h to obtain a precursor.

[0035] (2) The precursor was dispersed into 50 mL of a mixed solution of distilled water and ethanol in a volume ratio of 1:3, and refluxed at 90°C for reaction. After uniform dispersion, 4 mL of 0.05 mol / L ferric nitrate solution was added and refluxed and stirred for 5 h. After the reaction, a yellow precipitate was obtained. The precipitate was washed and dried to obtain a supramolecular assembly.

[0036] (3) Then, the supramolecular assembly was subjected to thermal polycondensation treatment. 0.2 g of the supramolecular assembly was placed in an atmosphere of a mixed gas of Ar / H2 (95% / 5%) by volume ratio, and the temperature was raised to 500°C at a rate of 0.5°C / min, kept at this temperature for 4 h, and then naturally cooled to room temperature to obtain the Fe@Fe-N3O-C catalyst. 4 mg of the catalyst sample was dispersed in a mixed solution containing 490 μL of ethanol, 490 μL of water, and 20 μL of 5 wt% Nafion solution; the dispersion was then ultrasonicated into a uniform ink-like slurry; 20 μL of the ink-like slurry was pipetted with a pipette and drop-coated on a rotating disk electrode (RDE) with a diameter of 5 mm, and then naturally dried at room temperature. The electrode of the drop-coated sample was used as the working electrode for subsequent electrochemical performance testing. Electrochemical test conditions: at room temperature, in an oxygen-saturated 0.1 M KOH solution. A three-electrode system was used, with a graphite rod as the counter electrode, a mercury-mercury oxide electrode as the reference electrode, and the RDE of the drop-coated sample as the working electrode.

[0037] Figure 1 This is the SEM image of Fe@Fe-N3O-C of this example. It can be seen that the catalyst material itself presents a wrinkled lamellar structure, which is conducive to the full exposure of the catalytic sites on the carrier surface.

[0038] Figure 2 The ORR performance diagram of Fe@Fe-N3O-C in this example shows that as the rotation speed increases, the limiting diffusion current density increases. When the scan rate is 5 mV / s and the disk electrode speed is 1600rpm, the catalyst's oxidative half-wave potential is 0.88 V and the starting potential is 0.95V, indicating that the prepared catalyst has an excellent catalytic effect.

[0039] Example 2 A method for preparing a bifunctional oxygen electrocatalyst with an asymmetric coordination structure comprises the following steps: (1) Weigh 0.76 g of melamine and disperse it in 60 mL of distilled water. Stir and dissolve it at 50°C to obtain solution A. Then add 4.8 mL of 0.45 mol / L citric acid solution and continue stirring to react for 60 min to obtain solution B. Then transfer solution B into a reactor for hydrothermal reaction at 110°C for 16 h. After the reaction is completed, a white precipitate is obtained. The precipitate is washed three times with distilled water and dried in a vacuum oven at 80°C for 12 h to obtain a precursor.

[0040] (2) The precursor was dispersed into 50 mL of a mixed solution of distilled water and ethanol in a volume ratio of 1:1, and refluxed at 80°C for reaction. After uniform dispersion, 8 mL of 0.01 mol / L cobalt nitrate solution was added and refluxed and stirred for 6 h. After the reaction, a pink precipitate was obtained. The precipitate was washed and dried to obtain a supramolecular assembly.

[0041] (3) Then, the supramolecular assembly was subjected to thermal polycondensation treatment. 0.2 g of the supramolecular assembly was placed in an atmosphere of a mixed gas of Ar / H2 (95% / 5%) by volume ratio, and the temperature was raised to 500°C at a rate of 0.5°C / min, kept at this temperature for 6 h, and then naturally cooled to room temperature to obtain the Co@Co-N3O-C catalyst. 4 mg of the catalyst sample was weighed and dispersed in a mixed solution containing 490 μL of ethanol, 490 μL of water, and 20 μL of 5 wt% Nafion solution; the dispersion was then ultrasonicated into a uniform ink-like slurry; 20 μL of the ink-like slurry was pipetted with a pipette and drop-coated on an RDE with a diameter of 5 mm, and then naturally dried at room temperature. The electrode of the drop-coated sample was used as the working electrode for subsequent electrochemical performance testing. Electrochemical test conditions: at room temperature, in an oxygen-saturated 0.1 M KOH solution. A three-electrode system was used, with a graphite rod as the counter electrode, a mercury-mercury oxide electrode as the reference electrode, and the RDE of the drop-coated sample as the working electrode.

[0042] Figure 3 This is the SEM image of Co@Co-N3O-C of this example. It can be seen that the catalyst material itself presents a uniform columnar structure. A large number of tiny nanotubes are loaded on the surface of the column, and no agglomerated nanoparticles are found, indicating that the dual ligand is conducive to promoting the dispersion of metal sites and ensuring a large reaction active area of ​​the catalyst.

[0043] Figure 4 The ORR performance diagram of Co@Co-N3O-C in this example shows that as the rotation speed increases, the limiting diffusion current density increases. At a scan rate of 5 mV / s and a disk electrode rotation speed of 1600 rpm, the catalyst's oxidogen half-wave potential is 0.86 V and the starting potential is 0.93 V, which confirms that the sample has excellent oxygen reduction performance.

[0044] Example 3 A method for preparing a bifunctional oxygen electrocatalyst with an asymmetric coordination structure comprises the following steps: (1) Weigh 2.27 g of melamine and disperse it in 60 mL of distilled water. Stir and dissolve it at 80°C to obtain solution A. Then add 16.5 mL of 1.1 mol / L citric acid solution and continue stirring to react for 10 min to obtain solution B. Then transfer solution B into a reactor for hydrothermal reaction at 148°C for 10 h. After the reaction is completed, a white precipitate is obtained. The precipitate is washed three times with distilled water and dried in a vacuum oven at 80°C for 12 h to obtain a precursor.

[0045] (2) The precursor was dispersed into 50 mL of a mixed solution of distilled water and ethanol in a volume ratio of 1:3, and refluxed at 90°C for reaction. After uniform dispersion, 18 mL of 0.1 mol / L cobalt nitrate solution was added and refluxed and stirred for 3 h. After the reaction, a pink precipitate was obtained. The precipitate was washed and dried to obtain a supramolecular assembly.

[0046] (3) The supramolecular assembly was then subjected to thermal polycondensation treatment. 0.2 g of the supramolecular assembly was placed in an atmosphere of a mixed gas of Ar / H2 (90% / 10%) by volume ratio, and the temperature was raised to 600°C at 2.5°C / min, kept at this temperature for 3 h, and then naturally cooled to room temperature to obtain the Co@Co-N3O-C catalyst. 4 mg of the catalyst sample was weighed and dispersed in a mixed solution containing 490 μL of ethanol, 490 μL of water, and 20 μL of 5 wt% Nafion solution; the dispersion was then ultrasonicated into a uniform ink-like slurry; 20 μL of the ink-like slurry was pipetted with a pipette and drop-coated on an RDE with a diameter of 5 mm, and then naturally dried at room temperature. The electrode of the drop-coated sample was used as the working electrode for subsequent electrochemical performance testing. Electrochemical test conditions: at room temperature, in an oxygen-saturated 0.1 M KOH solution. A three-electrode system was used, with a graphite rod as the counter electrode, a mercury-mercury oxide electrode as the reference electrode, and the RDE of the drop-coated sample as the working electrode.

[0047] Figure 5 This is the SEM image of Co@Co-N3O-C in this example. It can be seen that the catalyst material itself presents a uniform columnar structure, a large number of carbon particles are loaded on the surface of the column, and slight fractures occur in the radial direction of the column. These characteristics are conducive to ensuring good conductivity of the catalyst material and the diffusivity of ions in the oxygen reduction reaction, and improving the catalytic activity of the material.

[0048] Figure 6This is the ORR performance diagram of Co@Co-N3O-C in this example. It can be seen from the figure that as the rotation speed increases, the limiting diffusion current density increases. When the scan rate is 5 mV / s and the disk electrode rotation speed is 1600rpm, the catalyst's oxidative half-wave potential is 0.87 V and the starting potential is 0.97V.

[0049] Example 4 A method for preparing a bifunctional oxygen electrocatalyst with an asymmetric coordination structure comprises the following steps: (1) Weigh 1 g of melamine and disperse it in 60 mL of distilled water. Stir and dissolve it at 60°C to obtain solution A. Then add 10 mL of 0.625 mol / L citric acid solution and continue stirring to react for 30 min to obtain solution B. Then transfer solution B into a reactor for hydrothermal reaction at 120°C for 12 h. After the reaction is completed, a white precipitate is obtained. The precipitate is washed three times with distilled water and dried in a vacuum oven at 80°C for 12 h to obtain a precursor.

[0050] (2) The precursor was dispersed into 50 mL of a mixed solution of distilled water and ethanol in a volume ratio of 1:2, and refluxed at 85°C for reaction. After uniform dispersion, 4 mL of 0.05 mol / L cobalt nitrate solution was added and refluxed and stirred for 4 h. After the reaction, a pink precipitate was obtained. The precipitate was washed and dried to obtain a supramolecular assembly.

[0051] (3) Then, the supramolecular assembly was subjected to thermal polycondensation treatment. 0.2 g of the supramolecular assembly was placed in an atmosphere of a mixed gas of Ar / H2 (95% / 5%) by volume ratio, and the temperature was raised to 550°C at 2°C / min, and the temperature was kept for 4 h, and then the temperature was naturally cooled to room temperature to obtain the Co@Co-N3O-C catalyst. 4 mg of the catalyst sample was weighed and dispersed in a mixed solution containing 490 μL of ethanol, 490 μL of water and 20 μL of 5 wt% Nafion solution; the dispersion was then ultrasonicated into a uniform ink-like slurry; 20 μL of the ink-like slurry was dripped on a RDE with a diameter of 5 mm using a pipette, and then naturally dried at room temperature. The electrode of the dripped sample was used as the working electrode for subsequent electrochemical performance tests. Electrochemical test conditions: At room temperature, in an oxygen-saturated 0.1 MKOH solution. A three-electrode system was used, with a graphite rod as the counter electrode, a mercury-mercury oxide electrode as the reference electrode, and the RDE of the dripped sample as the working electrode.

[0052] Figure 7The SEM image of Co@Co-N3O-C of this embodiment shows that the catalyst material itself presents a uniform columnar structure, a large number of small carbon nanotubes are loaded on the surface of the column, and there are obvious fractures and holes in the radial direction of the column, and no agglomeration of metal particles is found. These characteristics are conducive to ensuring the good conductivity of the catalyst material and the diffusivity of ions in the oxygen reduction reaction, and improving the catalytic activity of the material.

[0053] Figure 8 This is the ORR performance diagram of Co@Co-N3O-C in this example. It can be seen from the figure that as the rotation speed increases, the limiting diffusion current density increases. At a scan rate of 5 mV / s and a disk electrode rotation speed of 1600rpm, the catalyst's oxidative half-wave potential is 0.91V and the starting potential is 0.99V, confirming the excellent catalytic activity of the material.

[0054] Fig. 9 This is the ORR stability performance diagram of Co@Co-N3O-C of this example. From the figure, it can be seen that after 20,000 cycles, the oxygen reduction potential of the catalyst has hardly changed, and the half-wave potential has only shifted to the left by 3 mV, indicating the good stability of the catalyst.

[0055] Fig.10 The OER performance diagram of the catalysts of Examples 1-4 is shown in FIG. As can be seen from the figure, the catalyst of Example 4 has the best OER performance, and its current density is 10 mA cm -2 , the overpotential is only 1.55 V. The catalyst of Example 1 has better performance, and its overpotential is 1.58 V. The OER performance of Examples 2 and 3 is slightly lower, and the overpotentials are 1.62 and 1.61 V, respectively, but still show good oxygen evolution function.

[0056] Catalyst zinc-air battery performance test The Co@Co-N3O-C material prepared in Example 4 was prepared into an ink-like catalyst and dropped on an area of ​​1 cm 2 On carbon paper with a hydrophobic diffusion layer, the mass loading was 1.5 mg cm -2 , and then dried at 60 °C for 6 h as an air cathode catalyst. The prepared air cathode was assembled with a 0.5 mm thick zinc sheet into a homemade metal-air battery, and the electrolyte was a mixed solution of 6 M KOH and 0.2 M Zn(NO3)2.

[0057] Fig.11 Polarization curve and power-density diagram of the zinc-air battery assembled with the catalyst prepared in Example 4. It can be seen from the figure that the zinc-air battery presents a high peak power density of 226.7 mW cm -2 .

[0058] Fig.12 The stability performance diagram of the zinc-air battery assembled with the catalyst prepared in Example 4 shows that after 240 hours of charge and discharge cycles, the battery still has a small charge and discharge voltage difference of 1V.

[0059] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a bifunctional oxygen electrocatalyst with an asymmetric coordination structure, characterized in that: The following steps are involved: S1, dispersing melamine in water and completely dissolving it at a preset temperature to obtain solution A, then adding citric acid solution and continuing to stir the reaction to obtain solution B; Then, solution B is subjected to a hydrothermal reaction, and a precipitate is obtained after the reaction is completed. The precipitate is washed and dried to obtain a precursor; S2, dispersing the precursor into a mixed solution of water and ethanol; performing a reflux reaction at a preset temperature, then adding an aqueous solution of transition metal ions, continuing the reflux reaction, obtaining a precipitate after the reaction is completed, washing the precipitate, and drying it to obtain a supramolecular assembly; S3. calcining the supramolecular assembly in an inert atmosphere, heating it to a holding temperature at a preset heating rate, holding it for a preset time, and then naturally cooling it to room temperature to obtain a bifunctional oxygen electrocatalyst with an asymmetric coordination structure.

2. The method for preparing a bifunctional oxygen electrocatalyst with an asymmetric coordination structure according to claim 1, characterized in that: In step S1, melamine is dispersed in water and completely dissolved at 50°C to 80°C. The concentration of the obtained solution A is 0.1 to 0.3 mol / L. The concentration of the citric acid solution is 0.45 to 1.1 mol / L. The molar ratio of melamine to citric acid is 1:(0.36 to 1). The stirring reaction time is 10 to 60 min.

3. The method for preparing a bifunctional oxygen electrocatalyst with an asymmetric coordination structure according to claim 1, characterized in that: In step S1, the temperature of the hydrothermal reaction is 110°C to 148°C, and the time is 8 to 16 hours.

4. The method for preparing a bifunctional oxygen electrocatalyst with an asymmetric coordination structure according to claim 1, characterized in that: In step S2, the volume ratio of water to ethanol in the water-ethanol mixed solution is 1:(1-3), the temperature of the reflux reaction is 80°C-90°C, and the time of the reflux reaction is 3-6 hours.

5. The method for preparing a bifunctional oxygen electrocatalyst with an asymmetric coordination structure according to claim 1, characterized in that: In step S2, the transition metal ion is a cobalt ion or an iron ion, the concentration of the transition metal ion aqueous solution is 0.01-0.1 mol / L, and the molar ratio of the transition metal ion to melamine is 1:(10-75).

6. The method for preparing a bifunctional oxygen electrocatalyst with an asymmetric coordination structure according to claim 1, characterized in that: In step S3, the inert atmosphere is an Ar / H2 mixed gas, and the volume ratio of Ar and H2 gas is (90%~95%) / (10%~5%).

7. The method for preparing a bifunctional oxygen electrocatalyst with an asymmetric coordination structure according to claim 1, characterized in that: In step S3, the preset heating rate is 0.5-2.5°C / min, the insulation temperature is 500-600°C, and the preset insulation time is 3-6h.

8. The method for preparing a bifunctional oxygen electrocatalyst with an asymmetric coordination structure according to claim 1, characterized in that: In step S3, the bifunctional oxygen electrocatalyst with an asymmetric coordination structure can catalyze oxidation and oxygen evolution reactions.

9. A bifunctional oxygen electrocatalyst with an asymmetric coordination structure, characterized in that: The method is prepared by any one of claims 1 to 8.

10. An application of the bifunctional oxygen electrocatalyst with an asymmetric coordination structure as claimed in claim 9, characterized in that: The bifunctional catalyst is used to prepare the cathode of zinc-air batteries.

Citation Information

Cited By

  • Piezoelectric functional material, piezoelectric functional material preparation method and water pollution treatment method

    CN122343098A